The effectiveness of graduated guidance on teaching leisure skills to children with autism spectrum disorder - KARAASLAN, ÖZCAN (My University, 2022)
The aim of this study was to investigate the effectiveness of teaching with graduated guidance on teaching the playing backgammon skill, which is one of the leisure skills, to children with ̈Autism Spectrum Disorder (ASD) ̈. Three children with ASD participated in this research. A multiple probe design across the participants was used in order to examine the effectiveness graduated guidance on teaching playing backgammon skill. The research was conducted by using. The dependent variable of this research is the level of acquiring playing backgammon skill. Additionally, the independent variable of this research is graduated guidance. According to the findings of this study, graduated guidance was effective on teaching playing backgammon skill, which is one of the leisure skills. In other words, result of this study revealed that graduated guidance was effective on teaching backgammon playing skill to children with ASD. In addition, it was determined that after finished instruction sessions, children with ASD were able to maintain the playing backgammon skill that they learned and also generalize the acquired skill to different person. In the light of the limitations identified and the findings, recommendations were made for further research.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Özel Eğitim; Social Sciences and Humanities; Education; Special Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, ÖZEL; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SPECIAL; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Autism Spectrum Disorder; Graduated Guidance; Leisure Skills; Playing Backgammon Skill; Autism Spectrum Disorder; Graduated Guidance; Leisure Skills; Playing Backgammon Skill